Sueño Bay adventures. 4, Candle Point - Deas, Mike, 1982-; Deas, Nancy (Deas, Mike, 1982- Sueño Bay adventures, 2023)
"When a wild winter storm rolls in and all the power goes out, Kay stays with her reclusive aunt, Gayle, the lighthouse keeper of Candle Point. On the long trek through the blustery snowstorm, Kay stumbles upon an injured moon creature. Kay smuggles her new friend into her aunt's lighthouse to take shelter from the cold. While exploring the lighthouse she discovers a network of tunnels and a colony of moon creatures. Kay tries to reunite the abandoned creature with its family but she can't do it alone. She tricks her friends into coming to the lighthouse and into the tunnel to help her reunite the hurt animal, but with no success. Desperate to heal her new friend, Kay plucks a mysterious moon crystal from the moon creatures' nest, an action that sets off a dangerous chain of events. The group becomes stranded when a cliff--and the bridge that leads in and out of Candle Point--collapses into the waves below. Can Kay regain the trust of her friends and restore the balance before Candle Point completely crumbles into the ocean? This is the fourth book in the Sue?o Bay Adventures series, following Shadow Island, Otter Lagoon and Hermit Hill."--Publisher.